Study of Kerr Soliton Microcombs in Optical Microresonators - Afridi, Adnan Ali (Trinity College Dublin. School of Physics. Discipline of Physics, 2022)
Microresonator-based Kerr optical frequency combs exhibit a spectrum of discrete and equally spaced frequency lines. The comb source is a precise frequency ruler to measure time and distance to extraordinary precision and therefore has been a hot topic of research for more than a decade. Since the discovery in 2007, a monolithic microresonator-based Kerr frequency comb (microcomb hereafter) generated via parametric four-wave mixing using a continuous-wave pump laser, emerged as an alternative scheme to large-scale fiber-based comb sources. Microresonators have attracted considerable interest due to miniaturization, chip-scale integration of pump and cavity, and spectral coverage from the visible to the mid-infrared. In recent years, the demonstration of novel dissipative Kerr solitons (DKS) in a microresonator was a tremendous breakthrough and revolutionized the field of microcomb technology because of the strong coherence, low noise (mode-locking), high stability, and broad spectral bandwidth of the soliton state. The Kerr solitons in a high-Q microcavity can be accessed under two crucial conditions. The first condition maintains the pulse shape with the balance between the dispersion and Kerr nonlinearity. The second condition that maintains the soliton is the loss in the cavity is compensated by the nonlinear parametric gain through the driving continuous wave laser. These prominent characteristics and a spectral width of an octave-spanning comb enable stable measurement of the comb via the self-referencing technique. This makes it an extraordinary candidate for monolithic integration in many commercial applications, particularly for timing and precision measurements. In this thesis, we thoroughly investigate the nonlinear dynamics in aluminum nitride (AlN) and silicon nitride (Si3N4) microresonators especially the microcomb generation and the soliton access. In particular, we proposed a reliable, universal scheme named dual-mode microresonators to access octave-spanning soliton microcombs, which is comparatively straightforward and cost-effective. With this method, we for the first time experimentally demonstrated a stable single-soliton (frep, 374 GHz) in an AlN microresonator with an octave-spanning (1100-2300 nm) comb owing to the engineered dispersion. Our highlight is the broad soliton existence range (SER, 10.4 GHz), which is 7 times greater than recently reported. This is quite useful for long-term stabilization thus enabling applications outside the laboratory, such as communication and LiDAR. In addition, with the aid of an external temperature controller, we successfully control the mode coupling, further extend the SER to 16 GHz and can reduce the carrier offset frequency (fceo) from ~40 to ~30 GHz with a decrease in temperature. The temperature controller can also be used to enrich the soliton dynamics, i.e., various two solitons state in this case. Thirdly, different soliton behavior such as the breather solitons and near-octave spanning soliton crystals were also experimentally observed in other dual-mode AlN devices due to the interaction of the two transverse mode families. Lastly, we confirm the robustness of the above-mentioned scheme in dual-mode Si3N4 microresonators with a fixed radius and obtained state-of-the-art results: single-soliton (frep, 1 THz) and various perfect soliton crystals (N= 4, 5, 6, 7, 8) with octave-spanning ranges. These solitons can be easily reached with a slow pump tuning rate. More importantly, the measurement results including the mode separation and dispersion agree with our simulation results very well. This indicates that such dual-mode microresonators can be designed and demonstrated with different material platforms.
APPROVED
Keywords: Kerr optical frequency combs; dual-modes scheme; dissipative Kerr-solitons; Microresonators; breather solitons; perfect soliton crystals.